Morphological transformation of soot: investigation of microphysical processes during the condensation of sulfuric acid and limonene ozonolysis product vapors - Soot particle mobility-mass relationship measurement - Pathak, Ravi Kant; Department of Chemistry & Molecular Biology, University of Gothenburg (University of Gothenburg, 2018)
The morphological transformation of soot particles via condensation of low-volatility materials constitutes a dominant atmospheric process with serious implications for the optical and hygroscopic properties, and atmospheric lifetime of the soot. We consider the morphological transformation of soot aggregates under the influence of condensation of vapors of sulfuric acid, and/or limonene ozonolysis products. This influence was systematically investigated using a Differential Mobility Analyzer-Aerosol Particle Mass Analyzer (DMA-APM) and the Tandem DMA techniques integrated with a laminar flow-tube system. We hypothesize that the morphology transformation of soot results (in general) from a two-step process, i.e., (i) filling of void space within the aggregate; (ii) growth of the particle diameter. Initially, the transformation was dominated by the filling process followed by growth, which led to the accumulation of sufficient material that exerted surface forces, which eventually facilitating further filling. The filling of void space was constrained by the initial morphology of the fresh soot as well as the nature and the amount of condensed material. This process continued in several sequential steps until all void space within the soot aggregate was filled. And then “growth” of a spherical particle continued as long as vapors condensed on it. We developed a framework for quantifying the microphysical transformation of soot upon the condensation of various materials. This framework used experimental data and the hypothesis of “ideal sphere growth” and void filling to quantify the distribution of condensed materials in the complementary filling and growth processes. Using this framework, we quantified the percentage of material consumed by these processes at each step of the transformation. For the largest coating experiments, 6%, 10%, 24% and 58% of condensed material went to filling process, while 94%, 90%, 76% and 42% of condensed material went to growth process for 75 nm, 100 nm, 150 nm and 200 nm soot particles, respectively. We also used the framework to estimate the fraction of internal voids and open voids. This information was then used to estimate the volume equivalent diameter of the soot aggregate containing internal voids and to calculate the dynamic shape factor, accounting for internal voids. The dynamic shape factor estimated based on the traditional assumption (of no internal voids) differed significantly from the value obtained in this study. Internal voids are accounted for in the experimentally derived dynamic shape factor determined in the present study. In fact, the dynamic shape factor adjusted for internal voids was close to 1 for the fresh soot particles considered in this study, indicating the particles were largely spherical. The effective density was strongly correlated with the morphological transformation responses to the condensed material on the soot particle and the resultant effective density was determined by the (i) nature of the condensed material; (ii) morphology and size of the fresh soot. In this work we quantitatively tracked in-situ microphysical changes in soot morphology, providing details of both fresh and coated soot particles at each step of the transformation. This framework can be applied to model development with significant implications for quantifying the morphological transformation (from the viewpoint of hygroscopic and optical properties) of soot in the atmosphere.

Purpose:

Study of morphological transformation of soot particles

Data is collected by instrument Differential Mobility Analyzer-Aerosol Particle Mass Analyzer (DMA-APM), program based on LabVIEW is used to control the instrument and log the data.

En omfattande studie av morfologisk omvandling av sotpartiklar (se abstrakt på engelska för detaljer)

Syfte:

Studie av morfologisk omvandling av sotpartiklar

Se beskrivning på engelska för detaljer
Morfologisk omvandling av sotpartiklar - Mätning av sotpartikel mobilitet-mass förhållande
Keywords: Soot; Sot; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap